The role of economic in natural resources development in the City of Baubau. (February 2019) - Abdullah, R; Pratiwi, ET; Abdullah, LOD; Dja'wa, A; Tenriawaru, A N; Fujaja, L
Abstract: Regional economic development is a process in which local governments and communities manage existing resources and form a partnership pattern between the government and the private sector to create new jobs or employment opportunities and stimulate economic growth. The purpose of the role of the Baubau City Economic and Natural Resource Development is to explain and inform the availability of data and information on the economic and natural resource development in the City of Baubau. The policy approach describes the vision and mission of the mayor so that the mayor has a very influential role in policymaking. Development policy in the City of Baubau is a non-radical continuing policy, more specifically the approach to be taken. Institutional procedures which are carried out with coordination and communication at high frequencies will significantly assist the smooth and successful planning and technical approach, studies of calculation criteria or methods to be used include natural resource balance and regional economic calculations.